Analysis of meristic characters of the Japanese threadfi n bream, Nemipterus japonicus (Bloch, 1791) along Indian coast - Sreekanth, G. B.; Chakraborty, Sushanta Kumar; Jaiswar, Ashok Kumar; Renjith, R. K.; Vaisakh, G.; Ail, Sunil S.; Kamei, G.; Pazhayamadom, Deepak George (Indian Journal of Fisheries, 2013)
The Japanese threadfi n bream, Nemipterus japonicus (Bloch, 1791) is a commercially important demersal fi sh species along the Indian coast especially in the maritime states of Kerala, Tamil Nadu, Maharashtra and Andhra Pradesh. In the present study, 389 samples were collected from four locations i.e., Cochin, Mumbai, Kakinada and Chennai and 15 meristic characters were recorded and analysed. Wald’s chi-square statistics was used to analyse the meristic characters. Most of the meristic characters showed no signifi cant difference between locations which depicted the similarity of stock collected from different locations. However, the counts of gill rakers were found signifi cant and important for differentiating the populations from these locations.